Multifractal downscaling of rainfall using Normalized Difference Vegetation Index (NDVI) in the Andes Plateau - Duffaut Espinosa, L.A.; Posadas, A.; Carbajal, M.; Quiróz, R. (Public Library of Science, 2017)
In this paper, a multifractal downscaling technique is applied to adequately transformed and lag corrected normalized difference vegetation index (NDVI) in order to obtain daily estimates of rainfall in an area of the Peruvian Andean high plateau. This downscaling procedure is temporal in nature since the original NDVI information is provided at an irregular temporal sampling period between 8 and 11 days, and the desired final scale is 1 day. The spatial resolution of approximately 1 km remains the same throughout the downscaling process. The results were validated against on-site measurements of meteorological stations distributed in the area under study.